Trigger survey approach to the evaluation of anxiety in patients with irritable bowel syndrome - Chuhunov, V. V.; Horodokin, A. D.; Kazakov, V. Ye.; Havrish, O. V. (Zaporozhye Medical Journal, 2023)
Irritable bowel syndrome (IBS) is one of the most common psychosomatic conditions affecting near 10 % of general population. Despite its relevance for today, there is no a unified approach to understanding its pathogenesis, it could be recognized as a complex somatoform reaction (based on the argument of extremely high comorbidity with anxiety and depressive conditions) or as a functional disorder (based on stereotypical clinical manifestations). The understanding of IBS as a psychosomatic condition as one that has combined psychopathogenesis seems to have the greatest perspectives in a clinical way. The study on psychological and behavioral components of IBS presents a promising area to understand ways of providing high-quality medical care for IBS patients. Aim. To systematize and evaluate the triggers of anxiety in patients with mixed form of irritable bowel syndrome. Materials and methods. A prospective study was conducted over a period of 2022–2023 including 100 patients with the main diagnosis of IBS. A distribution of IBS forms was as follows: 67 individuals with IBS-D (ICD-10: K58.1), 12 individuals with IBS-C (ICD-10: K58.2), 21 individuals with IBS-M (ICD-10: K58.3). They all were enrolled in the study as voluntary participants in a closed-ended online survey for IBS community support group. A mean age of IBS group was 38.5 ± 6.1 years. The comparison group was presented by 100 healthy volunteers without diagnosed pathology of gastrointestinal (GI) tract (or any GI-associated complains). A mean age of healthy volunteers was 29.5 ± 4.2 years. The study relied on the following methods: anamnestic, psychodiagnostic and statistical. Results. To structurally evaluate triggers of anxiety in patients with IBS we managed to distribute 23 separate triggers in 3 categories (social activity violations, eating habits and diet restrictions, health concerns). Each category was associated with features of a specific mental disorder: social activity violations – social anxiety disorder; eating habits and diet restrictions – avoidant and restrictive food intake disorder; health concerns – hypochondriasis. Anxiety level rating was collected according to the Likert scale in 5 ranks: “0” no anxiety (calm state); “1” – mild anxiety (slightly nervous); “2” – moderate anxiety (nervous); “3” – severe but controlled anxiety (very nervous or experiencing fear); “4” – uncontrolled anxiety (panicking). A distribution of anxiety levels for each trigger was determined and compared between healthy and IBS individuals. Conclusions. The analysis of the trigger set for social activity violations has shown a dominance of the formal setting and complexity of social situations in increasing the level of anxiety. The analysis of the trigger set related to eating habits and diet restrictions has shown that the formal setting, complicated social activity, and diet violations also tended to induce more intensive anxiety. The analysis of the health concern trigger set has revealed that sensations in the abdomen caused the most intensive cases of anxiety along with concerns about possible misdiagnosis of IBS.